PENERAPAN MODEL RECLIF DAN PROBLEM SOLVING MENINGKATKAN KEMAMPUAN METAKOGNITIF SISWA PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Aprillia Lustela; Handi Darmawan; Tesa Manisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine students’ metacognitive abilities after the implementation of ReCLif and Problem Solving learning models and to analyze the differences in metacognitive abilities on the topic of living organism classification in Grade VII of SMP Negeri 1 Sengah Temila. The study employed a quasi-experimental method with a Posttest-Only Control Group Design. Data were collected through a metacognitive ability test and analyzed using an Independent Sample t-Test. The results showed that students taught using the ReCLif model achieved a high level of metacognitive ability with an average percentage of 72.46% and a posttest score of 72.39. Students taught using the Problem Solving model also achieved a high level with an average percentage of 67.75% and a posttest score of 68.83. The t-test result indicated a significance value of 0.000 (<0.05), showing a significant difference between the two learning models. The ReCLif model was found to be more effective than the Problem Solving model in improving students’ metacognitive abilities.